Jejunal MALT (Mucosa Associated Lymphoid Tissue) Lymphoma: A Case Report - Alexandria Stephanie Suparman; Daniel Ardian Soeselo; Dyonesia Arie Harjanti (Indonesian Journal of Cancer, 2018)
Background: MALT (Mucosa Associated Lymphoid Tissue) Lymphoma is an uncommon condition. It is an involvement of extranodal site in hematologic malignancy, Non-Hodgkin Lymphoma.Case Presentation: Pondok Indah, Puri Indah Hospital Jakarta treated a 38-year-old female with acute abdomen due to jejunal MALT Lymphoma perforation, one meter from treitz ligament. Emergency laparotomy was performed, the patient had a resection and end to end anastomose. She was hospitalized in intensive care unit for 4 days after the surgery and died because of prolonged septic shock.Conclusions: MALT lymphoma is an uncommon condition which is often encountered in emergency conditions due to acute abdominal pain caused by intra-abdominal perforation of the hollow viscus. Late diagnosis and treatment may cause severe outcome such as perforation and hypovolemic shock. This case report is expected to provide insight and to increase the awareness of the incidence of jejunal MALT lymphoma in Indonesia.